2014
DOI: 10.1208/s12249-014-0085-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Freeze-Drying Process on the Physicochemical and Biological Properties of Pre-heated Amphotericin B Micellar Systems

Abstract: The moderate heat treatment of amphotericin B (AmB) in its micellar form (M-AmB) results in superaggregates (H-AmB) that present a substantially lower toxicity and similar activity. The aim of this work was to evaluate the H-AmB behavior after a freeze-drying process. H-AmB and M-AmB micelles were evaluated before and after freeze-drying concerning their physicochemical and biological properties by spectrophotometry and activity/toxicity assay, respectively. Four concentrations of M-AmB and H-AmB were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Cellular toxicity of amphotericin deoxycholate has been associated with aggregation of the drug, forming ion channels in cholesterol-containing membranes . Studies have indicated that “super-aggregates” of AmpB can overcome this limitation without losing anti- Leishmania activity. , In an effort to find more affordable but effective formulations of AmpB, a team compared the efficacy of super-aggregated forms of amphotericin deoxycholate to AmBisome. In this study, authors used heat treatment and separately microemulsions to induce super-aggregation of AmpB, which they confirmed using circular dichroism and spectroscopy.…”
Section: Formulations For the Treatment Of Vlmentioning
confidence: 99%
“…Cellular toxicity of amphotericin deoxycholate has been associated with aggregation of the drug, forming ion channels in cholesterol-containing membranes . Studies have indicated that “super-aggregates” of AmpB can overcome this limitation without losing anti- Leishmania activity. , In an effort to find more affordable but effective formulations of AmpB, a team compared the efficacy of super-aggregated forms of amphotericin deoxycholate to AmBisome. In this study, authors used heat treatment and separately microemulsions to induce super-aggregation of AmpB, which they confirmed using circular dichroism and spectroscopy.…”
Section: Formulations For the Treatment Of Vlmentioning
confidence: 99%